2000
DOI: 10.1128/jb.182.6.1659-1670.2000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Escherichia coli RecA Interactions with LexA, λ CI, and UmuD by Site-Directed Mutagenesis of recA

Abstract: An early event in the induction of the SOS system of Escherichia coli is RecA-mediated cleavage of the LexA repressor. RecA acts indirectly as a coprotease to stimulate repressor self-cleavage, presumably by forming a complex with LexA. How complex formation leads to cleavage is not known. As an approach to this question, it would be desirable to identify the protein-protein interaction sites on each protein. It was previously proposed that LexA and other cleavable substrates, such as phage CI repressor and E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…Once activated, RecA interacts with LexA protein, the repressor of the SOS genes (Wagner et al, 1999). This interaction triggers the autocatalytic cleavage of LexA and consequent destruction of its ability to function as a repressor, which results in the derepression of SOS genes (Mustard and Little, 2000;Fernandez De Henestrosa et al, 2000). By using DNA microarray techniques Courcelle et al (2001) have shown that in E. coli the expression of 43 genes is controlled by LexA.…”
Section: Sos Responsementioning
confidence: 99%
“…Once activated, RecA interacts with LexA protein, the repressor of the SOS genes (Wagner et al, 1999). This interaction triggers the autocatalytic cleavage of LexA and consequent destruction of its ability to function as a repressor, which results in the derepression of SOS genes (Mustard and Little, 2000;Fernandez De Henestrosa et al, 2000). By using DNA microarray techniques Courcelle et al (2001) have shown that in E. coli the expression of 43 genes is controlled by LexA.…”
Section: Sos Responsementioning
confidence: 99%
“…These proteins undergo autoproteolysis in vivo in a manner dependent on RecA, a protein involved in homologous recombination. The biological function of autocleavage is to inactivate these proteins (Mustard and Little 2000).…”
Section: The Umud Family Of Peptidasesmentioning
confidence: 99%
“…E. coli RecA activity is autoregulated by its C-terminus; deletion of the last 17 residues enhances most RecA activities (Cox, 2007a,b). For the region of E. coli RecA that corresponds to residues 240-255 of D. deserti RecAC, analysis of point mutations and structural data have established that residues in this region are implicated in coprotease substrate binding and cleavage (Dutreix et al, 1989;Mustard and Little, 2000;McGrew and Knight, 2003;VanLoock et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, one of the regions that are different in RecAC and RecAP, i.e. residues 240-255 (RecAC numbering), corresponds to a region in E. coli RecA that has been implicated in coprotease substrate binding and cleavage (Dutreix et al, 1989;Mustard and Little, 2000;McGrew and Knight, 2003;VanLoock et al, 2003). Therefore, the difference in this region of the RecA proteins might be an explanation for the inability of RecAP to induce TLS.…”
Section: Discussionmentioning
confidence: 99%